UPAYA MENINGKATKAN SELF-EFFICACY SISWA DALAM PEMBELAJARAN MATEMATIKA MELALUI PROBLEM BASED LEARNING - Nurdin Arifin (PENDAS MAHAKAM: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This research aims to improve self-efficacy and student learning outcomes grade X MIPA 3 senior high school in the academic year 2018/2019 linear equation system of three variables materials with model problem based learning.. This research was a classroom action research using Kemmis Mc Taggart desain. This research is a classroom action research conducted in two cycles, each of which comprises four stages: planning, action, observation, and reflection. The results of the students self-efficacy is an increase skor of 2,62. Mathematics learning outcomes totality from first cycle to the second cycle there is an increase of 38%. So, it can be concluded that by using the model problem based learning can increase the self-efficacy and results of class X MIPA 3 Senior high school in the academic year 2018/2019 in subject linear equation system of three variables